Bone marrow-derived mesenchymal stem cells from early diffuse systemic sclerosis exhibit a paracrine machinery and stimulate angiogenesis in vitro. Issue 11 (6th August 2011) - Guiducci, Serena; Manetti, Mirko; Romano, Eloisa; Mazzanti, Benedetta; Ceccarelli, Claudia; Dal Pozzo, Simone; Milia, Anna Franca; Bellando-Randone, Silvia; Fiori, Ginevra; Conforti, Maria Letizia; Saccardi, Riccardo; Ibba-Manneschi, Lidia; et al.
Abstract : Objective: To characterise bone marrow-derived mesenchymal stem cells (MSCs) from patients with systemic sclerosis (SSc) for the expression of factors implicated in MSC recruitment at sites of injury, angiogenesis and fibrosis. The study also analysed whether the production/release of bioactive mediators by MSCs were affected by stimulation with cytokines found upregulated in SSc serum and tissues, and whether MSCs could modulate dermal microvascular endothelial cell (MVEC) angiogenesis. Methods: MSCs obtained from five patients with early severe diffuse SSc (SSc-MSCs) and five healthy donors (H-MSCs) were stimulated with vascular endothelial growth factor (VEGF), transforming growth factor β (TGFβ) or stromal cell-derived factor-1 (SDF-1). Transcript and protein levels of SDF-1 and its receptor CXCR4, VEGF, TGFβ1 and receptors TβRI and TβRII were evaluated by quantitative real-time PCR, western blotting and confocal microscopy. VEGF, SDF-1 and TGFβ1 secretion in culture supernatant was measured by ELISA. MVEC capillary morphogenesis was performed on Matrigel with the addition of MSC-conditioned medium. Results: In SSc-MSCs the basal expression of proangiogenic SDF-1/CXCR4 and VEGF was significantly increased compared with H-MSCs. SSc-MSCs constitutively released higher levels of SDF-1 and VEGF. SDF-1/CXCR4 were upregulated after VEGF stimulation and CXCR4 redistributed from the cytoplasm to the cell surface. VEGF was increased by SDF-1 challenge. VEGF, TGFβ and SDF-1 stimulation upregulated TGFβ1, TβRI and TβRII in SSc-MSCs. TβRII redistributed from the cytoplasm to focal adhesion contacts. SSc-MSC-conditioned medium showed a greater proangiogenic effect on MVECs than H-MSCs. Experiments with blocking antibodies showed that MSC-derived cytokines were responsible for this potent proangiogenic effect. Conclusion: SSc-MSCs constitutively overexpress and release bioactive mediators/proangiogenic factors and potentiate dermal MVEC angiogenesis.